Peripheral neuropathic changes in pachyonychia congenita. Issue 12 (December 2016) - Pan, Baohan; Byrnes, Kelly; Schwartz, Mary; Hansen, C. David; Campbell, Claudia M.; Krupiczojc, Malvina; Caterina, Michael J.; Polydefkis, Michael
Abstract : Abstract: We compared patterns of intraepidermal nerve fibers and mechanoreceptors from affected and unaffected plantar skin from patients with pachyonychia congenita (PC) and control subjects. Plantar biopsies from 10 genetically confirmed patients with PC (with a mutation in KRT6A ) were performed at the ball of the foot (affected skin) and the arch (unaffected) and were compared to biopsies from corresponding locations in 10 control subjects. Tissue was processed to visualize intraepidermal nerve fibers (IENF) (PGP9.5), subsets of IENF (CGRP, substance P, tyrosine hydroxylase), myelinated nerve fiber (neurofilament H, NFH), blood vessels (CD31), Meissner corpuscles, and Merkel cells (MCs). Structures were quantified using stereology or validated quantification methods. We observed that PC-affected plantar skin had significantly lower sweat gland innervation (sweat gland nerve fiber density) and reduced numbers of Meissner corpuscles compared to PC-unaffected or anatomically matched control skin. In contrast, Merkel cell densities and blood vessel counts were higher in PC-affected skin compared to either control or PC-unaffected skin. There were no differences in myelinated nerve fiber densities, SP, or CGRP between the groups. Pressure pain thresholds in PC-affected skin were lower compared to PC-unaffected and anatomically matched control skin. Additionally, MC densities in callused plantar skin from healthy runners with callus and one subject with a nonpainful palmoplantar keratoderma ( AQP5 mutation) were similar to PC-unaffected and control skin consistent with callus alone not being sufficient to increase MC number. These findings suggest that alterations in PC extend beyond keratinocytes and may provide strategies to study neuropathic pain in PC. Abstract : Differences in nerve and mechanoreceptors exist in plantar skin biopsies from pachyonychia congenita patients vs controls. The results offer insight into potential biomarkers for pain.